2006
DOI: 10.1194/jlr.c500025-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mouse palmitoyl-coenzyme A Δ9-desaturase

Abstract: Stearoyl-coenzyme A desaturase (SCD) catalyzes the desaturation of saturated fatty acids to monounsaturated fatty acids in mammalian cells. Currently, there are four known enzymatic isoforms (SCD1-SCD4) in the mouse genome. The physiological roles for multiple SCD isoforms and their substrate specificities are unknown at present. We report here distinct substrate specificities for the mouse SCD isoforms. Each SCD isoform was able to complement the ole1 mutation in Saccharomyces cerevisiae through heterologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 26 publications
6
104
0
Order By: Relevance
“…SCD synthesizes oleic acid from stearate, a conversion that facilitates the biosynthesis of triglycerides and other neutral lipids. Four SCD genes have been cloned in mice, and SCD1 expression has been found to be highly correlated with liver steatosis (23). The hepatic mRNA levels of SCD1 were significantly higher in apoB/BATless versus apoB mice (apoB/BATless, 214.1 Ϯ 57.4%, n ϭ 4, versus apoB, 100 Ϯ 53.4%, n ϭ 4; p ϭ 0.03) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SCD synthesizes oleic acid from stearate, a conversion that facilitates the biosynthesis of triglycerides and other neutral lipids. Four SCD genes have been cloned in mice, and SCD1 expression has been found to be highly correlated with liver steatosis (23). The hepatic mRNA levels of SCD1 were significantly higher in apoB/BATless versus apoB mice (apoB/BATless, 214.1 Ϯ 57.4%, n ϭ 4, versus apoB, 100 Ϯ 53.4%, n ϭ 4; p ϭ 0.03) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, analysis of hepatic FA composition revealed decreases in the ratios of monounsaturated fatty acid MUFA to saturated fatty acid SFA , C16:1/C16:0 and C18:1/C18:0, in the mice fed SO, suggesting downregulation of SCD-1 activity in the liver. SCD-1, a downstream target of SREBP, is known to catalyze delta-9 desaturation of SFA such as C16:0 and C18:0 mainly in the liver and adipose tissue, and recent studies have shown a relationship between the high expression of SCD-1 and development of obesity and metabolic syndrome 38,39 . An earlier study demonstrated that suppression of SCD-1 by EPA prevents hepatic steatosis in diet-induced obese mice 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Scd1 and Scd2 expression is observed in a variety of lipogenic tissues, including liver and adipose tissue, Scd3 is primarily expressed in the skin, Harderian gland and preputial gland, and Scd4 is mainly expressed in the heart [5,6,9]. SCD3 is a palmitoyl-CoA desaturase with minimal desaturase activity towards stearoyl-CoA, while SCD1, SCD2, and SCD4 desaturate both palmitoyl-CoA and stearoylCoA to palmitoleoyl-CoA and oleoyl-CoA, respectively [11]. The physiological roles of Scd1 and Scd2 have been explored in mice with a targeted deletion of these genes [2,12].…”
Section: Multiple Isoforms Of Mouse and Human Scdmentioning
confidence: 99%